4: Peripheral Nerves Engage in Reciprocal Neuro- and Angiogenic Crosstalk With SMCs in Extremity Trauma. (July 2021) - Hwang, Charles D.; Pagani, Chase A.; Lee, Seungyong; Qin, Qizhi; Marini, Simone; Huber, Amanda; Meyers, Carolyn A.; Hespe, Geoffrey E.; Strong, Amy L.; Stepien, David M.; Sorkin, Michael; Nunez, Johanna; et al.
Abstract : Purpose: Existing literature describes the interdependence between neurotrophic and vascular signals in the central nervous system. We hypothesize a similar crosstalk important to extremity healing involving the peripheral nervous system and angiogenic cells. Nerves are difficult to capture via axons found in the periphery alone. Thus, we have interrogated from publicly available single-nuclei transcriptomic data of peripheral nerve soma (dorsal root ganglia), injured by physical transection or chemically induced pain. We present a combined analysis of extremity polytrauma (burn/tenotomy HO model) and peripheral nerve (post-injury/pain DRG model) to determine if there is expression of vascular signals by nerves and reciprocal neurotrophic signals by cells local to the injury site. Methods: A 30% dorsal burn and Achilles transection was performed in C57/BL6J mice. The tendon site tissues were harvested from baseline (t0) and day 7, 42 after induction. Samples were prepared for library generation on a 10x Genomics Chromium Controller, sequenced on a Illumina HiSeq 4000, and analyzed with Cell Ranger Software for pre-processing and alignment to the mm10 genome. DRG analyses and clusters were abstracted from NIH-GEO (GSE154659). Downstream analyses including unsupervised clustering downstream analyses were performed with Seurat. Results: We first examined candidate neurotrophins and vascular signals in nerve (DRG), finding robust upregulation of Bdnf and Vegfa . In HO, the site of injury contains many cells that may potentially respond to these signals. Indeed, in sequencing data from the pre-HO anlagen, endothelium and smooth muscle cell populations express upregulation for receptors to the nerve-derived Vegfa via Flt1 /VEGFR1. This population in addition to being sensitive to the VEGFA ligand, also demonstrates upregulation of Ngf, signifying a potential vasculo-neuro axis where a vascular signal induces endothelium/SMCs to produce neurotrophic signals. Completing the circuit, the original DRG cells and by logical extension, regenerating peripheral nerves, are highly enriched for the neurotrophin receptors: Ntrk1/ TrkA (responsive to the SMC derived NGF), Ntrk2/ TrkB (responsive to the nerve-autonomous BDNF), and Ntrk3/ TrkC (partial combined NGF/BDNF response). This potentially signifies a feedforward loop where peripheral nerve induces angiogenesis which in return, promotes nascent nerve ingrowth in a cyclical process. Indeed, in targeted knockout of a local VEGFA source ( Vegfa Prrx1 mice), the injury site demonstrates parallel reduction in vascular density (77%) and reduction in nerve fiber frequency (62%) within the HO site. Conclusions: These findings represent the first work characterizing the coordination between neurogenic and angiogenic transcription programs following extremity trauma. We demonstrate through NextGen sequencing, evidence of neuroangiogenic crosstalk following musculoskeletal/neural injury. This VEGFA/NGF axis involves vascular signaling as a potential source for additional proliferation of NGF expressing pericyte/SMCs. The presented data describe the potential nerve-driven regulation contributing to the formation of HO at the extremity that with antagonism or inhibition may lead to better treatments for aberrant extremity wound healing.